Policing Borders: Unauthorized Immigration and The Pernicious Politics of Attrition - Theodore, Nikolas (Social justice, 2011)
The article looks at immigration policy in the U.S., as of 2011, focusing on the shift of policy action with respect to undocumented immigrants from the federal level to the state and local levels, which the author terms rescaling. He outlines the passage and provisions of the 2010 Arizona Support Our Law Enforcement and Safe Neighborhoods Act, Senate Bill (SB) 1070. He discusses the law as exemplifying the attrition strategy adopted by anti-immigrant policymakers in the U.S., based on the idea that if daily life is made difficult enough for undocumented immigrants, they will self-deport, or return to their home countries. Topics include racism against Latinos in the U.S. and shifts in policing priorities.